Experimental transformation of the perception of colour - Abramovitz, Arnold (Department of Psychology, 2016)
This thesis presents an argument about the basis of our experience of colour. The argument is conducted by means of an interplay between a set of axioms, deductions from a particular theory (including "thought experiments" which explore the logic of those deductions), and concrete empirical evidence. The axioms and the theory are those of James G. Taylor. The title of the thesis refers to the general methodology adopted. The term "experimental transformation" carries specific connotations; and the notions from which it is derived, and to which it gives rise, have to be understood in the context of the total argument. If the argument presented is sound, then certain implications follow which, it is claimed, force us to reconsider many current assumptions about the nature of "colour sensation" and indeed about the very meaning to be ascribed to the term colour. This in turn would have significance for colour science, psychology and epistemology in general.